2013
DOI: 10.7554/elife.01229
|View full text |Cite
|
Sign up to set email alerts
|

Fitness benefits in fluoroquinolone-resistant Salmonella Typhi in the absence of antimicrobial pressure

Abstract: Fluoroquinolones (FQ) are the recommended antimicrobial treatment for typhoid, a severe systemic infection caused by the bacterium Salmonella enterica serovar Typhi. FQ-resistance mutations in S. Typhi have become common, hindering treatment and control efforts. Using in vitro competition experiments, we assayed the fitness of eleven isogenic S. Typhi strains with resistance mutations in the FQ target genes, gyrA and parC. In the absence of antimicrobial pressure, 6 out of 11 mutants carried a selective advant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
106
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(108 citation statements)
references
References 58 publications
2
106
0
Order By: Relevance
“…Other factors, such as the host's diet, could also play a role in maintaining intrinsic antibiotic resistance genes, because foods (45) such as sweet potatoes and coffee contain caffeic acid, a compound that has an antimicrobial activity toward P. aeruginosa (46). In conclusion, the findings that intrinsic and acquired antibiotic resistance genes are associated with increased in vivo fitness of P. aeruginosa, A. baumannii, and V. cholerae in four different experimental infection settings, along with recent reports about the lack of fitness costs associated with antibiotic resistance in S. enterica serovar Typhimurium (47) and E. coli (48), emphasize the necessity to effectively control the emergence of antibiotic-resistant pathogens as well as the development of alternative approaches to prevent and treat infections. Last, our findings point to additional potential consequences, wherein virulent strains of serious microbial pathogens that are both more drug-resistant and more pathogenic may be establishing themselves as the predominant organisms able to infect at-risk humans.…”
Section: Discussionmentioning
confidence: 88%
“…Other factors, such as the host's diet, could also play a role in maintaining intrinsic antibiotic resistance genes, because foods (45) such as sweet potatoes and coffee contain caffeic acid, a compound that has an antimicrobial activity toward P. aeruginosa (46). In conclusion, the findings that intrinsic and acquired antibiotic resistance genes are associated with increased in vivo fitness of P. aeruginosa, A. baumannii, and V. cholerae in four different experimental infection settings, along with recent reports about the lack of fitness costs associated with antibiotic resistance in S. enterica serovar Typhimurium (47) and E. coli (48), emphasize the necessity to effectively control the emergence of antibiotic-resistant pathogens as well as the development of alternative approaches to prevent and treat infections. Last, our findings point to additional potential consequences, wherein virulent strains of serious microbial pathogens that are both more drug-resistant and more pathogenic may be establishing themselves as the predominant organisms able to infect at-risk humans.…”
Section: Discussionmentioning
confidence: 88%
“…Studies with whole-genome sequencing of global Salmonella serovar Typhi collections have shown that a particular haplotype, H58, is more likely to be MDR and to have intermediate susceptibility to ciprofloxacin (530,531). This haplotype has become dominant in many regions and may have a competitive advantage compared with other haplotypes (532)(533)(534)(535)(536).…”
Section: Fluoroquinolonesmentioning
confidence: 99%
“…Notably, 11 of the 18 MDR S. Typhi isolates from Bangladesh analyzed in this study have developed resistance to high-level fluoroquinolone by alterations in gyrase A (S83F and D87G) and enhanced efflux pumps (9). High-level fluoroquinolone resistance on salmonellae may have a prohibitive fitness cost (29); however, fluoroquinolone-resistant S. Typhi strains may have a fitness benefit even in the absence of antimicrobial pressure (30). Thus, intensive surveillance is necessary to monitor the dissemination of the S. Typhi strains that bear chromosome-mediated resistance to multiple first-line antimicrobials and fluoroquinolone for the treatment of typhoid fever.…”
mentioning
confidence: 99%